Melchizedek in Hebrews 7 - Granerød, Gard 1975- (2009)
Hebrews has more to say about Melchizedek than what is said about him in LXX Ps 109,4 (perhaps also MT Ps 110,4) and Genesis 14. Heb 7,3 says that Melchizedek is “without father, without mother, without genealogy, having neither beginning of days nor end of life” and that “he remains a priest forever”. I discuss where the author gets this information from. Methodologically, priority should be given to an explanation made on the basis of the hermeneutical techniques that the author uses elsewhere. I argue that the surplus information found in Heb 7,3.8 stems from arguments made from silence. The author explicitly makes arguments from silence in Heb 7,14.20.
Keywords: Hebrews 7; Psalms 109,4; Genesis 14; Melchizedek